THE ROLE OF WOMEN IN REALIST FICTION - Eldorbek Erkin og’li Khamitov; Markabaeva Mexriban Keulimjayevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This study focuses on the role of women in realist fiction and explains how female characters are used to present real life and social reality. In realist literature, women often become central figures because their daily experiences clearly show the problems existing in society. Unlike romantic or ideal characters, women in realist works are portrayed as realistic individuals with ordinary lives, responsibilities, and difficulties. Female characters in realist fiction belong to various social backgrounds and perform different roles, such as mothers, wives, daughters, and workers. Through these roles, authors demonstrate how social rules and traditions influence women’s lives and limit their freedom. At the same time, realist writers give much attention to women’s inner world, showing their emotions, thoughts, and personal struggles. These characters help reveal social injustice, inequality between men and women, and moral challenges. Moreover, women’s lives in realist fiction often reflect wider social issues. Their personal stories are connected with problems such as economic hardship, forced marriage, lack of rights, and limited access to education. Some realist works also present women as strong personalities who try to change their situation and seek independence despite social pressure. To sum up, women play an essential role in realist fiction because they help portray society in a truthful and realistic way. Through female characters, authors express criticism of social systems and raise important questions about justice, morality, and the status of women. Therefore, the depiction of women remains a significant element of realist literature.